Did the 2011 Nabro eruption affect the optical properties of ice clouds?. Issue 18 (23rd September 2015) - Meyer, A.; Vernier, J.‐P.; Luo, B.; Lohmann, U.; Peter, T.
Abstract: The eruption of the Eritrean Nabro Volcano in June 2011 was the largest eruption since Mount Pinatubo in June 1991. The Nabro volcano emitted 1–1.5 megaton of sulfur dioxide into the lower stratosphere which resulted in a significant rise in the stratospheric sulfate aerosol burden in the months following the eruption. We have analyzed backscatter and extinction from ice clouds, as measured by the Cloud‐Aerosol Lidar and Infrared Pathfinder Satellite Observations (CALIPSO) satellite between June 2006 and May 2014, to assess if volcanic aerosol produced by the Nabro eruption had affected ice clouds. We found no significant modifications of either of ice cloud optical properties (i.e., total backscattering and extinction), occurrence frequencies, or residence altitudes on a global scale. Using the analyzed optical properties as indicators of posteruptive ice cloud radiative forcing modifications, we find that the eruption had no significant volcanic aerosol‐ice cloud radiative effect. Our results suggest that the investigated optical properties of ice and cirrus clouds are at most weakly dependent on the sulfate droplet number density and size distribution. Key Points: Nabro had no significant effect on ice cloud properties, frequency, and altitude No significant volcanic aerosol‐ice cloud radiative effect after Nabro Ice cloud properties depend at most weakly on sulfate droplet abundance and size